PROGRAM PENDIDIKAN KARAKTER DALAM PENGEMBANGAN KEWIRAUSAHAAN SISWA SEKOLAH MENENGAH SCHOOL OF UNIVERSE BOGOR - Irfan Setiawan; Eka Suhardi; Sumardi Sumardi (Universitas Pakuan, 2021)
CHARACTER EDUCATIONAL PROGRAM OF ENTREPRENEURSHIP DEVELOPMENT OF SENIOR HIGH SCHOOL STUDENT AT SCHOOL OF UNIVERSE BOGOROne of the facts of the problem in our country recently is the large number of unemployed, due to lack of employment. Based on CNBC Indonesia's news source, October 30, 2019 the Indonesian (society) prefers to become an online motorcycle or taxi driver because of the gap in applying for another job. People who already got a job often become an online motorcycle or taxi drivers for additional income. To overcome these various problems of education, this people need an educational method which is most effective in character building. Nowadays, there are many educational experts in some regions in Indonesia managing to develop educational institutions which are certainly unique and able to stimulate student character formation. Entrepreneurship is one of the educational characters which can be the point of economic movement of the nation. Entrepreneurship is needed for the progress of the nation's economy, because by entrepreneurship the nation will be able to build up an individual independency attitude. It is aimed to reducing the sense of the dependent on others, thus providing a great opportunity to create jobs and reduce unemployment. The School of Universe (SoU) to combining some methods that should be carried out by a school that requaring his pupil progression by using the concept of nature and directing students to their interests and talents. In this case, SoU focuses students on entrepreneurship development with a number of views on some world prominent business and also supported by technology facilities. By these programs, Indonesia is expected to get a generation that will be able to create jobs so as to reduce the number of unemployement. It is also expected to be a new breakthrough idea of Indonesia to organize a better education system. The administer of entrepreneurship development system of The school of Universe covered some contents of learning processes, learning resources, and the collaborative networks with institutions that support the school.